Seismic behaviour of self-centring braced frame buildings with reusable hysteretic damping brace. - Zhu, Songye
This paper presents the seismic behaviour of a concentrically braced frame system with self-centring capability, in which a special type of bracing element termed reusable hysteretic damping brace (RHDB) is used. The RHDB is a passive energy dissipation device with its core energy-dissipating component made of superelastic Nitinol wires. Compared with conventional bracing in steel structures, RHDB has a few prominent performance characteristics: damage free under frequent and design basis earthquakes in earthquake prone areas; minimal residual drifts due to the self-centring capability of RHDB frame; and ability to survive several strong earthquakes without the need for repair or replacement. This paper also includes a brief discussion of the RHDB's mechanical configuration and analytical model for RHDB. The seismic performance study of RHDB frame was carried out through a non-linear time history analysis of 3-storey and 6-storey RHDB frame buildings subjected to two suites of 20 earthquake ground motions. The analysis results were compared with buckling-restrained brace (BRB) frames. This study shows that RHDB frame has a potential to outperform BRB frames by eliminating the residual drift problem.
Keywords: Energy dissipation; Damper; Self-centring.; Seismic response; Shape memory alloy; Structural control